Experiencia pedagógica creativa: expresión corporal, educación musical y currículo escolar y preescolar - Arguedas Quesada, Consuelo (2004)
Creativity is an crucial tool in the development of a man's and a woman's personality. It frees themselves from fear of making mistakes and promotes the acceptance for new goals or experiences, invites them to explore and be respectful and tolerant, encourages individual and group work, arousing originality in their responses to the different conflicts they may have to face. In addition, it indicates the creating potential within each person, which should be respected but also stimulated, without limiting the individual's spontaneity. Such ideas are present in the “Workshop of Body Expression and Music for the Teachers of the First Cycle of Basic General Education”, which was given in different educational centers of the provinces of Cartago and San José. When encouraging creativity through strategies of body expression and musical education integrated to the school curriculum, a “motivation chain” towards their students is created, so they can also develop their creative capacity to enable significant learning.